Characterization of Nanoparticle Intestinal Transport Using an In Vitro Co-Culture Model - Strugari, Alina F.G. (Nanomaterials (Basel), 2018)
We aimed to obtain a tunable intestinal model and study the transport of different types of nanoparticles. Caco-2/HT29-MTX co-cultures of different seeding ratios (7:3 and 5:5), cultured on Transwell® systems, were exposed to non-cytotoxic concentration levels (20 μg/mL) of silicon quantum dots and iron oxide (α-Fe(2)O(3)) nanoparticles. Transepithelial electric resistance was measured before and after exposure, and permeability was assessed via the paracellular marker Lucifer Yellow. At regular intervals during the 3 h transport study, samples were collected from the basolateral compartments for the detection and quantitative testing of nanoparticles. Cell morphology characterization was done using phalloidin-FITC/DAPI labeling, and Alcian Blue/eosin staining was performed on insert cross-sections in order to compare the intestinal models and evaluate the production of mucins. Morphological alterations of the Caco-2/HT29-MTX (7:3 ratio) co-cultures were observed at the end of the transport study compared with the controls. The nanoparticle suspensions tested did not diffuse across the intestinal model and were not detected in the receiving compartments, probably due to their tendency to precipitate at the monolayer surface level and form visible aggregates. These preliminary results indicate the need for further nanoparticle functionalization in order to appropriately assess intestinal absorption in vitro.